Relationship between personality and physical activity: a behavior genetic analysis - Vukasović Hlupić, Tena (Array, 2014)
The aim of this study was to explore the relationship between personality and physical activity (PA) in a sample of Croatian twins. Data were collected from 339 twin pairs (105 MZ and 234 DZ) aged between 15 and 22 years. On the phenotypic level there are significant correlations between PA and two personality traits: neuroticism (r = -.23) and extraversion (r = .17). Univariate analyses indicate substantial heritability of PA. Bivariate analyses indicate that there is a negative genetic correlation (rA= -.27) between PA and neuroticism, and a positive genetic correlation between PA and extraversion (rA= .45), meaning that the same genetic factors contributing to higher neuroticism also contribute to lower PA, and the same genetic factors contributing to higher extraversion also contribute to higher PA. Results of Cholesky decomposition indicate that heritable differences in PA are only in part accounted for by the genetic architecture of neuroticism and extraversion.